Potential for cardiac toxicity with methylimidazolium ionic liquids - Tarek M. Abdelghany; Shireen A. Hedya; Carol De Santis; Sahar S. Abd El-Rahman; Jason H. Gill; Noha F. Abdelkader; Matthew C. Wright (Ecotoxicology and Environmental Safety, 2023)
Methylimidazolium ionic liquids (MILs) are solvent chemicals used in industry. Recent work suggests that MILs are beginning to contaminate the environment and lead to exposure in the general population. In this study, the potential for MILs to cause cardiac toxicity has been examined. The effects of 5 chloride MIL salts possessing increasing alkyl chain lengths (2 C, EMI; 4 C, BMI; 6 C; HMI, 8 C, M8OI; 10 C, DMI) on rat neonatal cardiomyocyte beat rate, beat amplitude and cell survival were initially examined. Increasing alkyl chain length resulted in increasing adverse effects, with effects seen at 10−5 M at all endpoints with M8OI and DMI, the lowest concentration tested. A limited sub-acute toxicity study in rats identified potential cardiotoxic effects with longer chain MILs (HMI, M8OI and DMI) based on clinical chemistry. A 5 month oral/drinking water study with these MILs confirmed cardiotoxicity based on histopathology and clinical chemistry endpoints. Since previous studies in mice did not identify the heart as a target organ, the likely cause of the species difference was investigated. qRT-PCR and Western blotting identified a marked higher expression of p-glycoprotein-3 (also known as ABCB4 or MDR2) and the breast cancer related protein transporter BCRP (also known as ABCG2) in mouse, compared to rat heart. Addition of the BCRP inhibitor Ko143 – but not the p-glycoproteins inhibitor cyclosporin A - increased mouse cardiomyocyte HL-1 cell sensitivity to longer chain MILs to a limited extent. MILs therefore have a potential for cardiotoxicity in rats. Mice may be less sensitive to cardiotoxicity from MILs due in part, to increased excretion via higher levels of cardiac BCRP expression and/or function. MILs alone, therefore may represent a hazard in man in the future, particularly if use levels increase. The impact that MILs exposure has on sensitivity to cardiotoxic drugs, heart disease and other chronic diseases is unknown.